2016
DOI: 10.1016/j.celrep.2016.03.042
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-Derived Mutations Both Inhibit HIV-1 Replication and Accelerate Viral Escape

Abstract: Cas9 cleaves specific DNA sequences with the assistance of a programmable single guide RNA (sgRNA). Repairing this broken DNA by the cell's error-prone non-homologous end joining (NHEJ) machinery leads to insertions and deletions (indels) that often impair DNA function. Using HIV-1, we have now demonstrated that many of these indels are indeed lethal for the virus, but that others lead to the emergence of replication competent viruses that are resistant to Cas9/sgRNA. This unexpected contribution of Cas9 to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
205
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(215 citation statements)
references
References 38 publications
8
205
1
1
Order By: Relevance
“…Most indels within the target will likely create a resistance allele as well. Importantly, the driver itself is expected to produce its own resistance alleles when cleavage is repaired by end joining mechanisms such as nonhomologous end joining (NHEJ) or microhomology-mediated end joining, rather than homologous recombination, and such resistance alleles have already been observed in several experiments (Gantz and Bier 2015;Hammond et al 2016;Wang et al 2016).…”
mentioning
confidence: 99%
“…Most indels within the target will likely create a resistance allele as well. Importantly, the driver itself is expected to produce its own resistance alleles when cleavage is repaired by end joining mechanisms such as nonhomologous end joining (NHEJ) or microhomology-mediated end joining, rather than homologous recombination, and such resistance alleles have already been observed in several experiments (Gantz and Bier 2015;Hammond et al 2016;Wang et al 2016).…”
mentioning
confidence: 99%
“…One widely discussed approach is the use of gene editing to eliminate integrated virus(s) or virus receptors. When it comes to integrated viral genomes, a major problem with gene editing is that the editing process accelerates the generation of replication-competent viral escape mutants that are now resistant to Cas9/sgRNA, thereby greatly limiting its potential for HIV therapy (9). Because our approach is not genetic, viral escape would have to involve development of an alternative route for virus entry into cells that is unlikely and, if it happened, would be expected to be highly inefficient and selected against at the population level.…”
Section: Discussionmentioning
confidence: 99%
“…While editing of T cells had shown promise for HIV resistance, two independent publications demonstrated NHEJ-mediated viral escape of Cas9/gRNA suppression [134, 135]. Sequencing of escaped viral mutants identified that the mutations clustered around the gRNA target cleavage site where indels are formed.…”
Section: Applicationsmentioning
confidence: 99%